A lone voice in the wilderness? Persistent problems with victim support in Czechia: Samotny głos wołającego na pustyni? Utrzymujące się problemy w zakresie wspierania pokrzywdzonych w Czechach (Archives of Criminology, 2025)
This article examines the challenges in implementing victim support in Czechia and highlights discrepancies between legislative frameworks and practical applications. The study employs a mixed-methods approach, including a focus group conducted in 2017 with experts in victim support and an expert survey in 2022. While the 2013 adoption of the Act on Victims of Crime led to notable improvements in victims’ rights and services, persistent problems include ineffective information delivery, regional disparities in service provision and a lack of inter-agency coordination. The article concludes that while legislative reforms have laid a solid foundation, systemic changes and practical implementation are essential to ensuring effective victim support and mitigating secondary victimisation.